Época de semeadura de milho doce no Noroeste do Paraná - Franco, Antonio Augusto Nogueira (2015)
The main feature of the sweet corn is possessing genes that are expressed in the endosperm to block the conversion of sugars in starch, giving the sweet character. This feature adds value to the product, and this has been increasing, with growing demand in Brazil. However, there is a lack of information about the influence of sowing time on the development of sweet corn, causing farmers use recommendations suggested for the common corn, which are not always ideal. Sowing time at the right time, although does not have any effect on the cost of production, affects the phenotypic response of plants, mainly characteristics associated with yield and, consequently, the profit of the farmer. In this context, the objective of this study was to evaluate the effect of sowing times on the performance of sweet corn hybrids grown in Summer and Autumn/Winter periods, with additional irrigation in Maringá, Northwest of the Paraná State, Brazil. The design used was randomized complete block, in factorial scheme, with four replications. The treatments were constituted by combination of sowing times (Summer period - 09/05, 09/19, 10/03, 10/17 and 10/31; Autumn/Winter period - 02/18, 03/04, 03/18 and 04/01) and two sweet corn hybrids (Tropical Plus and RB6324) in two agricultural years (2011 and 2012). Were evaluated growth phytotechnical characteristics (plant height and leaf area index); of the yield component (number of kernels per row, number of row of kernels per ear and yield of marketable ears) and chemical composition of kernels (total sugars, starch and protein content). The data were submitted to conjunct variance analysis. The effects of sowing times were studied by analysis of polynomial regression and the effects of agricultural years and hybrids were studied by F test. The vegetative growth was limited by delay at the sowing times, affecting the production components and chemical composition of the sweet corn kernels. RB6324 hybrid showed higher yield potential than Tropical Plus hybrid, mainly on unwanted weather. The phenological cycle of the RB6324 and Tropical Plus hybrids are similar and the delay at the sowing time extended the number of days to harvest, milky grains phenological stage. In summer period, the number of days to harvest was 91 days for the first sowing time (09/05) and 84 days for the last sowing time (10/31). In Autumn/Winter period, the number of days between sowing and milky grains stage, were respectively 93 and 120 days for the first (02/18) and last (04/01) sowing time. The delay at the sowing time did not provide variation on the accumulation of degree-days by the hybrids among sowing times, agricultural years and cultivation periods. The thermal time accumulation in the period between sowing - VT (tasseling) and between VT - milky grains stage, were respectively 858 and 301 degree-days. The use of the irrigation system was essential to replace the daily evapotranspiration in all sowing times, growing seasons and years of study. The first half of the month of October and the second half of the month of February are respectively the best times for sweet corn sowing in Summer and Autumn/Winter periods in Northwestern Paraná State, Brazil.